Former Ratonian celebrates 100th Once knew 'Kid' (Raton, New Mexico Raton Range)
Newspaper Article on the 100th birthday of Jose Mendoza.
Master list item #: 49
File location is in the Raton File Cabinet
Keywords: Billy the Kids; Mendoza, Jose; Padilla, Louis; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Walsenburg, Colorado; Las Vegas, New Mexico; Santa Fe, New Mexico